KINERJA INDUK KELINCI REX DENGAN UMUR PENYAPIHAN YANG BERBEDA - , MUHAMMAD TAUFIQ ALAMSYAH; , Panjono., S.Pt., MP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted to observe the rabbit does performance at different weaning ages. This research used 12 heads of rabbit does which divided randomly into three goups of weaning age, i.e, 4, 5, and 6 weeks. The rabbits were raised in the individual cage. After giving a birth, rabbit does were raised together with their bunnies prior to the weaning age. After weaning, rabbit does was moved to the male cage for mating. Data obtained were analyzed using one way ANOVA. The results of the research showed that there were no significantly different litter size, birth weight, weaning weight, and pre weaning mortality, among groups. Kindling interval of rabbit does which weaned at four weeks of age was shorter (P<0,05) than does which weaned at five and six weeks. It is concluded that the weaning age does not affect litter size, birth weigth, weaning weight, and pre weaning mortality, but affects the kindling interval. Earlier weaning age, gave shorter kindling interval.